Treeline dynamics in relation to climatic variability in the central Tianshan Mountains, northwestern China - Wang, Ting; Zhang, Qi-Bin; Ma, Keping (Global ecology and biogeography, 2006)
Aim: Climate variability may be an important mediating agent of ecosystem dynamics in cold, arid regions such as the central Tianshan Mountains, north-western China. Tree-ring chronologies and the age structure of a Schrenk spruce (Picea schrenkiana) forest were developed to examine treeline dynamics in recent decades in relation to climatic variability. Of particular interest was whether tree-ring growth and population recruitment patterns responded similarly to climate warming. Location: The study was conducted in eight stands that ranged from 2500 m to 2750 m a.s.l. near the treeline in the Tianchi Nature Reserve (43°45'-43°59' N, 88°00'-88°20' E) in the central Xinjiang Uygur Autonomous Region, northwestern China. Methods: Tree-ring cores were collected and used to develop tree-ring chronologies. The age of sampled trees was determined from basal cores sampled as close as possible to the ground. Population age structure and recruitment information were obtained using an age-d.b.h. (diameter at breast height) regression from the sampled cores and the d.b.h. measured on all trees in the plots. Ring-width chronologies and tree age structure were both used to investigate the relationship between treeline dynamics and climate change. Results: Comparisons with the climatic records showed that both the radial growth of trees and tree recruitment were influenced positively by temperature and precipitation in the cold high treeline zone, but the patterns of their responses differed. The annual variation in tree rings could be explained largely by the average monthly minimum temperatures during February and August of the current year and by the monthly precipitation of the previous August and January, which had a significant and positive effect on tree radial growth. P. schrenkiana recruitment was influenced mainly by consecutive years of high minimum summer temperatures and high precipitation during spring. Over the last several decades, the treeline did not show an obvious upward shift and new recruitment was rare. Some trees had established at the treeline at least 200 years ago. Recruitment increased until the early 20th century (1910s) but then decreased with poor recruitment over the past several decades (1950-2000). Main conclusions: There were strong associations between climatic change and ring-width patterns, and with recruitments in Schrenk spruce. Average minimum temperatures in February and August, and total precipitation in the previous August and January, had a positive effect on tree-ring width, and several consecutive years of high minimum summer temperature and spring precipitation was a main factor favouring the establishment of P. schrenkiana following germination within the treeline ecotone. Both dendroclimatology and recruitment analysis were useful and compatible to understand and reconstruct treeline dynamics in the central Tianshan Mountains.